Human identification at a distance using body shape information - Alang Md Rashid, Nahrul Khair; Yahya, M. F.; Shafie, Amir Akramin (IOP Publishing, 2013)
Shape of human body is unique from one person to another. This paper presents an intelligent system approach for human identification at a distance using human body shape information. The body features used are the head, shoulder, and trunk. Image processing techniques for detection of these body features were developed in this work. Then, the features are recognized using fuzzy logic approach and used as inputs to a recognition system based on a multilayer neural network. The developed system is only applicable for recognizing a person from its frontal view and specifically constrained to male gender to simplify the algorithm. In this research, the accuracy for human identification using the proposed method is 77.5. Thus, it is proved that human can be identified at a distance using body shape information.